2015
DOI: 10.1007/s11575-015-0238-7
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Overseas Acquisitions by Indian Firms? A Behavioral Risk-Taking Perspective

Abstract: This version of the article has been accepted for publication, after peer review (when applicable) and is subject to Springer Nature's AM terms of use, but is not the Version of Record and does not reflect post-acceptance improvements, or any corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 69 publications
3
102
0
2
Order By: Relevance
“…Knowledge acquisition and exploitation by EMNEs follow the conventional view that treats the firm as an institution for integrating knowledge (Grant, 1991, Grant, 1996 and supports the evolving body of research on EMNEs' internationalization which suggests that the EMNE possesses managerial skills (Chittoor, Aulakh, & Ray, 2015), the capacity to absorb external knowledge , Kotabe, Jiang, & Murray, 2011, and the ability to bundle country specific advantages with their own firm specific advantages (Hennart, 2009). Our findings have implications for the Uppsala model (Johanson & Vahlne, 1977, Johanson & Vahlne, 2009, Johanson & Wiedersheim-Paul, 1975 as we examine the EMNE's strategies of amassing and exploiting learning and knowledge that enable it to surmount the intermediate stages of internationalization.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Knowledge acquisition and exploitation by EMNEs follow the conventional view that treats the firm as an institution for integrating knowledge (Grant, 1991, Grant, 1996 and supports the evolving body of research on EMNEs' internationalization which suggests that the EMNE possesses managerial skills (Chittoor, Aulakh, & Ray, 2015), the capacity to absorb external knowledge , Kotabe, Jiang, & Murray, 2011, and the ability to bundle country specific advantages with their own firm specific advantages (Hennart, 2009). Our findings have implications for the Uppsala model (Johanson & Vahlne, 1977, Johanson & Vahlne, 2009, Johanson & Wiedersheim-Paul, 1975 as we examine the EMNE's strategies of amassing and exploiting learning and knowledge that enable it to surmount the intermediate stages of internationalization.…”
Section: Introductionmentioning
confidence: 62%
“…Learning and building on knowledge from prior internationalization moves such as exporting and importing, appear to be the key strategy employed by the EMNE (Aulakh, Kundu, & Lahiri, 2014, Peng, 2012. Among other factors, such as the ownership structure and managerial skills (Chittoor, Aulakh, & Ray, 2015), market knowledge enhances the EMNEs risk-taking ability. Without such market knowledge and learning, in-house resources may not be productively utilized by the EMNE.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be the result of Indian managers' vast experience of managing within a diverse home country (Kumar, 2008) and foreign education and experience of working abroad (Chittoor et al, 2015). We acknowledge that our measurement for managerial skills is based on manager's salary.…”
Section: Resultsmentioning
confidence: 99%
“…However, in recent years some Indian MNEs are competing successfully in dynamic modern technology-intensive industries. In a recent study, Chittoor, Aulakh, and Ray (2015) reported that foreign education and experience of Chief Operating Officers of Indian MNEs have enabled them to undertake acquisitions of foreign firms. It is further argued that Indian managers and entrepreneurs have the ability to deliver "value for money" and the skills to succeed despite India's geographic and cultural diversity (Kumar, 2008, p. 251) and that this is an important internationally transferable skill.…”
Section: Managerial Resourcesmentioning
confidence: 99%